Anisotropiy of magnetic susceptibility and fault-slip dat study in late cenozoic rocks exposed in the southwest border of puna plateau (27º30´S) - Quiroga Carrasco, Rodrigo Adolfo (2022)
We present new Anisotropy of Magnetic Susceptibility (AMS) analysis integrated with structural analysisof fault slip data to document a strain fi eld change from syndepositional to post depositional deformationduring the late Eocene to Pliocene times, in the southwest margin of Puna Plateau (SWPP) and north areas inthe Argentine Precordillera (Pc, 27º30´S, Fig. 1). We obtained 10 AMS sites carried out in late Eocene-early Oligocene sedimentary rocks in the SWPP and 6 AMS sites in early Pliocene sedimentary and volcaniclasticrocks exposed in Pc (Figs. 1A and 1B, respectively). The measurements show low to high values of anisotropydegree (P= 1,00-1,16) in the deformation zones, and low and high values of bulk susceptibility (with an averageof 11.9x10-3 SI). The magnetic fabric is the type I and II, according to Robion et al. (2007), in most of thesites, with a shape parameter whose values show an oblate to prolate shape (T=-0,8 to 0,9), with a weak towell-developed magnetic lineation in some sites. We estimate two main orientations of magnetic lineation,a ~N-S and E-W, in the SWPP, and a NS orientation in the Pc area (Figure 1). We compare the orientationof magnetic lineation with the structural features and with maximum horizontal stress directions (SHmax)obtained from fault-slip inversion (FSI) data obtained using the Wintensor software (Delvaux and Sperner2003) (Quiroga et al., in prep.). In the west area of SWPP the NS-oriented magnetic lineation is parallelto the orientation of folds and reverse faults that aff ect the early Oligocene sequences, and orthogonal tothe E-W compression direction estimated from the FSI obtained from mesoscale reverse fault measured inthese rocks, and strike-slip faults aff ecting the Pliocene volcanic rocks exposed in the area (Fig. 1A) (Quirogaet al. in prep.). In the East sector of this area (SWPP), the magnetic lineation is NW oriented, parallel tothe main strike of structures that conform a strike-slip fault system, and reverse faults with N-S and NNEcompression directions. The activity of these structures started after the middle Miocene times (Quiroga etal. in prep). In the North Pc, the magnetic foliation is parallel with the restored bedding plane orientationof Pliocene sequences. The incipient magnetic lineation is NS-oriented, parallel to the NS-strike of foldsand faults that are aff ecting the Pliocene sequences (Fig. 1B), parallel to paleocurrents documented inthe same sequences, and orthogonal to the E-W compression documented between the upper Miocene andlower Pliocene (Quiroga et al. 2021).We interpret a tectonic origin for magnetic lineation in the SWPP, documenting an E-W contraction,parallel to the regional SHmax that aff ected the Central Andes during the Eocene Incaic orogeny. In the Pcarea, the magnetic fabric was developed in a sedimentary setting whose incipient magnetic lineation maydocument an E-W syndepositiontal contraction direction, parallel to the regional Incaic E-W compression.Since ~5 Ma, a shift in the compression direction towards a N-S orientation is interpreted to be related to thelocal-third-order stress fi eld that aff ects the entire south margin of the Puna Plateau along its transition tothe Frontal Cordillera and Sierras Pampeanas (Quiroga et al. 2021). This shifting could be a consequence ofthe Pliocene uplift of the southern Puna, generating a juxtaposition of an area under N-S extension, in thetopographically-higher Puna, with the lower areas outside of the limit of this plateau under N-S compression.